Postgraduate Programmes -- SMU Infographics - Singapore Management University (Institutional Knowledge at Singapore Management University, 2014)
SMU offers a wide range of postgraduate programmes designed to nurture a new generation of leaders with the regional perspectives, insights and expertise needed to drive Asia’s economies and societies forward. View this for a snapshot of all the programmes available, and how each of them will transform you professionally and personally.